Influência do contra-íon molibdênio nas propriedades do pigmento SnO2: Cr - Silva, Renata Ferreira Lins da (2008)
SnO2 pigments, when doped with chromium, lead to violet or purple colors, depending on chromium oxidation state. There is a need to control the chromophore oxidation state, as Cr(VI) is toxic and carcinogenic, while Cr(III) leads to no risk to living beings. Cr(VI) formation may be avoided with the addition of counterions, that lead to a charge imbalance. In this work, SnO2:Cr pigments were synthesized by the polymeric precursor method, with the addition of molybdenum as counterion. The powder precursor decomposition was evaluated by thermogravimetry (TG) and differential thermal analysis (DTA). The influence of the counterion in the crystalline structure was evaluated by Xray diffraction. The materials were also characterized by infrared spectroscopy, colorimetry and UV-vis spectroscopy. All pigments are crystalline and single phase with cassiterite structure. Chromium formation with hexavalent state was observed in all samples, while Sn0.90Cr0.06Mo0.04O2 presented the lowest amount of this cation, comparing to the other pigments, being the less toxic one. Violet and rose colors were obtained for materials doped with chromium and chromium/molybdenum, respectively, being related to the formation of Cr(IV) in the material structure.